(untitled) (Research, Society and Development, 2024)
Objective: This systematic review aimed to evaluate the effectiveness of the application of injectable Hyaluronic Acid (HA) gel as a therapy for the regeneration of deficient interdental papillae. Methodology: The SALSA framework strategy was used, performing a search in four digital databases: Ebsco, PubMed, Science Direct and Scielo, where articles in English and Spanish, published in the last five years (2018-2023), were collected. Results: Eighteen studies were included with a total of 213 participants and 696 interdental papillary defects. All included studies reported promising results on reconstruction of deficient interdental papilla after HA injection. Conclusion: The short-term analysis indicated that HA injection for the treatment of papillary defects is considered a feasible treatment achieving satisfactory aesthetic results with minimal pain. However, more well-conducted RCT studies with standardized parameters and long-term follow-up should be recommended.